Evaluasi Bukti dari Uji Klinis tentang Interaksi Antibiotik dan Antasida: Suatu Tinjauan Sistematis Literatur - Al Qindy, Wildan Hidayah; Nurdin, Fitri Oktaviani; Khaerunisa, Aulia; Putri, Meisya Diffa Amalia; Hilmi, Indah Laily; Putri, Mukarromah Dita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Drug interactions between antibiotics and antacids represent an important clinical issue that can affect therapeutic efficacy and increase the risk of treatment failure. The concurrent use of these drug classes frequently occurs in clinical practice, particularly in patients receiving antibiotic therapy who also present with gastrointestinal complaints. This systematic literature review aims to evaluate the clinical trial evidence regarding antibiotic–antacid interactions, focusing on pharmacokinetic and pharmacodynamic mechanisms, clinical implications, and current research limitations. Relevant articles were identified through PubMed, Google Scholar, and other scientific databases using standardized keywords. Literature selection followed the PRISMA guidelines to ensure the quality and relevance of included studies. The analysis revealed that antacids and proton pump inhibitors (PPIs) can significantly reduce the bioavailability of antibiotics, especially fluoroquinolones and tetracyclines, through chelation with metal ions and by increasing gastric pH, thereby impairing drug absorption. Concomitant use of antibiotics and PPIs was also associated with a higher risk of Clostridioides difficile infection (CDI), particularly in elderly or comorbid patients. Conversely, newer acid-suppressing agents such as vonoprazan demonstrated good efficacy in Helicobacter pylori eradication regimens without compromising antibiotic activity. Despite these findings, most studies were retrospective, with limited sample sizes and specific populations. Therefore, large-scale prospective clinical trials are needed to strengthen the evidence base. A comprehensive understanding of antibiotic–antacid interactions is essential to support rational, safe, and effective prescribing practices in clinical settings.